Package Tracking Information System Enterprise Architecture Modeling Using TOGAF ADM - Izdihar Abhista Ramadhani; Yupie Kusumawati (Sistemasi: Jurnal Sistem Informasi, 2022)
PT. Pos Indonesia engaged in the logistics of sending letters and goods which has its head office in Bandung and has 11 regional offices spread throughout Indonesia, one of them is Semarang. The main function of the Semarang Postal Processing Center is as a post processing office which has a central point in Semarang to connect each region. Such as Delivery Centers (DC) Demak, Mranggen, Tugu, Erlangga, Banyumanik, and others, so they must go through the Semarang Post Processing Center first before being forwarded to the recipient or destination office. In supporting the business process, the Indonesian Post Office already has a package tracking system that can be accessed on the Pos Indonesia website so that consumers do not have to go to the nearest Post Office. The package tracking system aims as a system that can facilitate consumers in tracking packages. The problem in the package tracking system is that it is less accurate and efficient in tracking because it can't track packages on maps and consumers don't get automatic notification notifications when the package will be delivered and the package will arrive soon. In dealing with this, the author proposes to make improvements to the business process by designing an Enterprise Architecture (EA) package tracking system using the TOGAF ADM method, with research results in the form of an IT blueprint as a guideline to accelerate employee performance, improve services to consumers and be able to provide changes. business processes effectively.